2020
DOI: 10.1177/0890117120908511
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Improve Sexual and Reproductive Health in US Active Duty Military Service Members: A Systematic Review

Abstract: Objective: To identify and describe behavioral interventions to promote sexual and reproductive health among US active duty military service members. Data Sources: Systematic searches of PubMed, CINAHL, and PsychINFO (N = 1609 records). Inclusion Criteria: English-language articles published between 1991 and 2018 and retrieved using search terms related to military service, interventions, and sexual and reproductive health. Exclusion Criteria: Articles excluded if not empirically based, not published in peer-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
(146 reference statements)
0
1
0
1
Order By: Relevance
“…Demikian pula, intervensi berbasis bukti memainkan peran penting dalam meningkatkan kesehatan seksual dan reproduksi remaja di negaranegara berpenghasilan rendah dan menengah, dengan menekankan pentingnya dampak berkelanjutan dan hasil yang adil (Salam et al, 2016). Selain itu, intervensi perilaku, termasuk yang disampaikan melalui platform media sosial, telah menunjukkan efektivitas dalam mempromosikan kesehatan seksual dan reproduksi di kalangan populasi tertentu, seperti anggota militer AS (Vargas et al, 2020;Henderson, 2023).…”
Section: Promosi Kesehatan Reproduksiunclassified
“…Demikian pula, intervensi berbasis bukti memainkan peran penting dalam meningkatkan kesehatan seksual dan reproduksi remaja di negaranegara berpenghasilan rendah dan menengah, dengan menekankan pentingnya dampak berkelanjutan dan hasil yang adil (Salam et al, 2016). Selain itu, intervensi perilaku, termasuk yang disampaikan melalui platform media sosial, telah menunjukkan efektivitas dalam mempromosikan kesehatan seksual dan reproduksi di kalangan populasi tertentu, seperti anggota militer AS (Vargas et al, 2020;Henderson, 2023).…”
Section: Promosi Kesehatan Reproduksiunclassified
“…The simple adaptation of a civilian behavioral intervention program may not be successful, given the complexity, mobility, and diversity of the U.S. military population [ 6 ]. A recent review spanning 1991–2018 found a total of 8 published reports on interventions designed to decrease STIs among US military personnel, only 3 of which included STI incidence as an outcome measure [ 15 ]. Of these, only one study, published in 2005 and conducted with only female marine recruits on a single military base, demonstrated intervention efficacy in decreasing incident STIs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%